Pemahaman penyakit menular seksual (PMS) pada murid yang tinggal di Panti Asuhan dengan non Panti Asuhan - Albert, Bernadict Charlie Davin; Setiawan, Antonius Ian Bayu (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2024)
Sexually transmitted diseases are increasingly prevalent in tandem with evolving times and more liberal social interactions. This study aims to: understand the differences in knowledge of sexually transmitted diseases (STDs) between students living in orphanages and those not living in orphanages, identify the high rate of sexually transmitted disease transmission and assist teachers in providing education, and propose guidance topics related to understanding sexually transmitted diseases. This is a quantitative descriptive comparative study with a sample of all students at Xaverius Baturaja High School, totaling 101 students, consisting of 40 students living in orphanages and 61 students not living in orphanages. The analysis techniques include categorization, normality test, homogeneity test, and Mann Whitney U-test. The results showed a low level of understanding with no significant difference between the two groups of students, although students in orphanages had a higher level of understanding. Then provide suggestions to teachers in providing education.